MEDIASI PENAL SEBAGAI UPAYA DALAM RANGKA PEMBAHARUAN HUKUM PIDANA DI INDONESIA BERBASIS NILAI-NILAI KESEIMBANGAN - Taufiqurrohman Abildanwa (UNISSULA, 2016)
The purpose which would be expected in ”Penal Mediation” in positive criminal law which is to root the values promoted by restorative justice is rooted in traditional values in traditional societies such as the value of balance, harmony and peace in society. This study used library research (library research) with normative approach to determine the policy of the criminal law in the prevention of criminal acts through efforts to settle outside the court process in order to reform the criminal law in Indonesia. Analysis of the data used in this study is qualitative data analysis of the primary data and secondary data. Results of this study were (1) the criminal law policy in combating criminal acts through efforts to resolve extrajudicial positive today only a small part, while others are still oriented to the formal completion. (2) Policy criminal law in combating criminal acts through the efforts of a settlement Penal Mediation in the framework of criminal law reform in Indonesia should be arranged in an integrated manner, and the required type of criminal that could compromise or take advantage of the positive aspects (the reverse also means, avoid negative terms) on the other side of the prison and criminal surveillance sector on the other side.